2005
DOI: 10.1007/s11269-005-0129-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Accumulation and Other Components of the Groundwater in Relation to Cropping System in an Aquifer in Southwestern Spain

Abstract: Inappropriate farming techniques and 4 years of drought (1992)(1993)(1994)(1995) produced conditions for high nitrate concentration in an aquifer located in the Province of Seville (Southwest Spain). The objectives of this study were to study groundwater components and to determine the relationship between the cropping system and nitrate concentrations in groundwater. From October 1994 to May 1996, 16 groundwater samples were obtained from a network of 35 sample points. Groundwater concentrations were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Also, inappropriate farming techniques and crop types (e.g. potatoes) have a significant contribution to nitrate pollution and salinization (González Vázquez et al 2005). Approximately 20% of irrigated land is moderately or severely affected by salinization (Douaoui & Hartani 2007).…”
mentioning
confidence: 99%
“…Also, inappropriate farming techniques and crop types (e.g. potatoes) have a significant contribution to nitrate pollution and salinization (González Vázquez et al 2005). Approximately 20% of irrigated land is moderately or severely affected by salinization (Douaoui & Hartani 2007).…”
mentioning
confidence: 99%
“…A common practice for managing water scarcity is the alternative of irrigation using treated/undertreated wastewater. This practice has brought significant benefits in terms of increasing availability of good quality water to high priority, meeting agricultural water resulted in important levels of nitrates in groundwater [35]- [39]. Even if wastewater is generally low in nitrate, it contains significant levels of ammonium compounds that convert via nitrification process into nitrate, which later leach into groundwater.…”
Section: Study Areamentioning
confidence: 99%
“…González Vázquez et al (2005) reported that inappropriate farming techniques and four years of drought (1992)(1993)(1994)(1995) produced high nitrate concentration conditions in an aquifer located in the Province of Seville, southwest Spain. The study showed the impact of crops and the cropping system on groundwater quality.…”
Section: Water and Soil Quality In Selected Arid And Semi-arid Regionmentioning
confidence: 99%